The relationship between high performance work system and turnover intention : A generation gap study - Asrul Effendy Ismail (2015)
This study focused on highly skilled employees turnover intention in a construction company. Most construction projects are difficult and complex to manage.The high turnover rate of high skilled employees can affect the output and performance of construction companies. This research studies the characteristics of Generation X and Generation Y employees in the construction industry in Sabah, Malaysia. Data collected are 161 valid respondents. Based on the survey, the highest respondent’s age group falls is Gen Y which between 37 years old and below (55.6 percent) and the lowest is Gen X which 38 years old and above (44.4 percent). To address the above issues, this study aims to identify the effectiveness of human resource management practices in facilitating the study of relationship between High Performance Work System (HPWS), psychological empowerment, employee engagement and turnover intentions. Thus, to achieve the objectives of this study, a quantitive method was applied. Data were analyzed using SPSS and "Smart PLS Version 2.0". The results show that High Performance Work System has a significant and positive effect on turnover intention and mediate the relationships between employee engagement and turnover intention. These findings can provide evidence and persuade construction companies in Sabah sepecifically and Malaysia generally to increase the employee engagement and in the same time to reduce employee turnover rates especially among high skills employees. When companies invest in employees, they should also take care of the individual’s and family needs, by doing so, employees would feel engaged. In the future, the scope of the study may be expanded to enhance the reliability of this study.